Governance and Management of Religious Tourism in India - Kiran Shinde (International Journal of Religious Tourism and Pilgrimage)
Religious tourism constitutes the dominant form of tourism in India and yet little is known about how it is governed and managed. This paper aims to contribute to a better understanding of governance and management of religious tourism. It first provides an overview of policy framework and governance mechanisms that are relevant for religious tourism. Then a market profile is presented to examine how the religious tourism economy intersects with the state-apparatus of policies and institutions. To better explain the complexities of religious tourism, the paper employs the axis of formal-informal economy: the informal end is where the religious tourism economy is based on the traditional practice of pilgrimage, that relies on the informal networks built around social patronage relationships between visitors and religious actors; while at the formal end, it is often the state-sponsored and/or public charitable trusts that act as corporate religious bodies for providing and organising a range of services in religious tourism. Detailed studies of two sites - Vrindavan and Shirdi - provide the empirical data. The pilgrimage-town of Vrindavan in the state of Uttar Pradesh in north India represents the former; the pilgrimage town of Shirdi in the western state oreligious tourism. Detailed studies of two sites - Vrindavan and Shirdi - provide the empirical data. The pilgrimage-town of Vrindavan in the state of Uttar Pradesh in north India represents the former; the pilgrimage town of Shirdi in the western state of Maharashtra is an example of the latter. Vrindavan is associated with traditional religious practice and sacred geography pertaining to the Hindu god Krishna while Shirdi is dedicated to a 20th century saint, Sai Baba. Consequently, the former involves elaborate rituals and performances while the latter is fairly limited in terms of visitors’ engagement, and exhibits more mass-tourism-like features. The analytical triad of religious geography - specialists - performances is used to explore the range of management systems involved in the religious tourism of the two sites. It is found that the transformations of the religious tourism economy from a traditional pilgrimage practice bring in uneasy tensions: while religious actors actively participate in promotion and management of the religious tourism economy at local levels, they hardly shoulder responsibilities of addressing the negative environmental impacts. Thus, there is often an ‘institutional vacuum’ in dealing with both direct and indirect impacts of religious tourism. The paper shows how the reality of religious tourism is at odds with the state’s envisioned role since it largely operates beyond the state-policy framework. The paper argues that identifying the formal and informal systems in management can help to better address the multi-faceted impacts of religious tourism and contribute in developing measures for its sustainability.